Certification - just obey the rules! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A medicinal herb grower from South Africa describes the process of cleaning and certifying her farm for organic production, and the potential for other farmers.